Answer:
y = 11
Explanation:
First, you would get rid of the 52 from the left side of the equation. So you would subtract 52. Doing this, you also have to be fair to the other side of the equation and subtract 52 from that side as well:
52 - 2y - 52 = 30 - 52
- 2y = -22
To get rid of the coefficent (-2), since you multiply -2 by y to get -2y, you divide -2y by -2, therefore leaving y. As i stated before you have to be fair, so you must divide -22 by -2 and then you are left with the value of y.
-2y/-2 = -22/-2
y = 11
To check, you just plug in 11 in place of y:
52 - 2 x 11 = 30
52 - 22 = 30
30 = 30